Fetal membrane bacterial load is increased in histologically confirmed inflammatory chorioamnionitis: A retrospective cohort study. (February 2020) - Hockney, Rochelle; Waring, Gareth J.; Taylor, Gillian; Cummings, Stephen P.; Robson, Stephen C.; Orr, Caroline H.; Nelson, Andrew
Abstract: Introduction: It is widely debated whether fetal membranes possess a genuine microbiome, and if bacterial presence and load is linked to inflammation. Chorioamnionitis is an inflammation of the fetal membranes. This research focussed on inflammatory diagnosed histological chorioamnionitis (HCA) and aimed to determine whether the bacterial load in fetal membranes correlates to inflammatory response, including histological staging and inflammatory markers in HCA. Methods: Fetal membrane samples were collected from patients with preterm spontaneous labour and histologically phenotyped chorioamnionitis (HCA; n = 12), or preterm (n = 6) and term labour without HCA (n = 6). The bacterial profile of fetal membranes was analysed by sequencing the V4 region of the 16S rRNA gene. Bacterial load was determined using qPCR copy number/mg of tissue. The association between bacterial load and bacterial profile composition was assessed using correlation analysis. Results: Bacterial load was significantly greater within HCA amnion (p = 0.002) and chorion (p = 0.042), compared to preterm birth without HCA. Increased bacterial load was positively correlated with increased histological staging (p = 0.001) and the expression of five inflammatory markers; IL8, TLR1, TLR2, LY96 and IRAK2 (p=<0.050). Bacterial profiles were significantly different between membranes with and without HCA in amnion (p = 0.012) and chorion (p = 0.001), but no differences between specific genera were detected. Discussion: Inflammatory HCA is associated with infection and increased bacterial load in a dose response relationship. Bacterial load is positively correlated with HCA severity and the TLR signalling pathway. Further research should investigate the bacterial load threshold required to generate an inflammatory response in HCA. Highlights: Increased bacterial load was significantly associated with inflammation. Bacterial load is correlated with HCA severity in a dose dependent manner. Bacterial load is correlated to the TLR signalling pathway. Non-HCA samples and negative controls are not distinct in bacterial load.